JARINGAN TERORIS SOLO DAN IMPLIKASINYA TERHADAP KEAMANAN WILAYAH SERTA STRATEGI PENANGGULANGANNYA (STUDI DI WILAYAH SOLO, JAWA TENGAH) - , FAJAR PURWAWIDADA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Terrorism committed by force and violence in the name of God in the name of religion continues to happenin Indonesia. One of them as a terrorist network Solo. This study aims to identify and understand the development of this tissue from forming, and its management implications. Issues raised in this study is how the formation of terrorist networks Solo, the cause of terrorism, characteristics and implications for regional security and mitigation strategies. This research is a descriptive qualitative social. Source of data used include primary data and secondary data. The technique of collecting data using interviews, observations, and supported the study documentation. Qualitative data analysis is done with the data reduction, data display and conclusion. The study was conducted in Solo. Based on the results of this study showed that the formation of a network of Solo terrorism can not be separated from the influence of the Darul Islam that mutated into a radical Islamic groups and terrorist groups continue to be new. The main cause is a political motive wrapped in religion and other factors supported. Characteristics of the new network in the Solo group is still an amateur compared to the old group, although with the same ideology. While acts of terrorism in Solo implications on the security of the region especially the ideological, political, economic, social and human security. Combating terrorism in Solo has managed to capture and dismantle terrorist networks Solo new, but there are still many weaknesses that need to be repaired. Effective counter-terrorism strategy conducted in Solo is through law enforcement, prevention, de radicalization and disengagement, which must be programmed properly and is a shared responsibility.